PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PROYEK BERBASIS WEBSITE (STUDI KASUS : PELAKSANAAN PROYEK KONSTRUKSI DI PT. DWIWAHANA DELTA MEGAH) - Muhamad Wahyudi; Pratikso; M. Faiqun Ni’am (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Along with the rapid progress of Internet technology and the ease of access to the use of the current technology,. Making web-based applications using HTML and PHP programming with MySQL is used as database server. Feedback and input from potential users can contribute to the improvement and development of information system to be realized.The resulting system provides up to date information about the progress of work every week through the Dashboard page that is inputted by the companies, system archiving project documents are integrated and can be accessed online at any time by the parties involved. History activities both problems and solutions during project execution recorded on this website through the discussion and photos, so it can be a reference for the planning and implementation of similar projects later.Data and information and documents stored in server storage ease and speed but it also serves as a document backup / backup of physical documents / hardcopies in digital form. In addition to understanding the implementation of the project, the response and feedback from potential users are very helpful in the development of the website. Needs improvement features that already exist and the addition of new features which match to project owner needs so that the project management information system based on this website can be function optimally.